Effects of treatment with corticosteroids on human rhinovirus-induced asthma exacerbations in pediatric inpatients: a prospective observational study - Kan-o, Keiko; Washio, Yasuyoshi; Oki, Takeshi; Fujimoto, Tsuguto; Ninomiya, Takahito; Yoshida, Makoto; Fujita, Masaki; Nakanishi, Yoichi; Matsumoto, Koichiro (BMC pulmonary medicine, 2023)
Human rhinoviruses (HRVs) infection is a common cause of exacerbations in pediatric patients with asthma. However, the effects of corticosteroids on HRV-induced exacerbations in pediatric asthma are unknown. We conducted a prospective observational study to determine the viral pathogens in school-age pediatric inpatients with asthma exacerbations. We assessed the effects of maintenance inhaled corticosteroids (ICS) on the detection rates of HRV species and treatment periods of systemic corticosteroids during exacerbations on pulmonary lung function after exacerbations. Nasopharyngeal samples and clinical information were collected from 59 patients with asthma exacerbations between April 2018 and March 2020. Pulmonary function tests were carried out 3 months after exacerbations in 18 HRV-positive patients. Changes in forced expiratory volume in 1 second (FEV )% predicted from baseline in a stable state were compared according to the treatment periods of systemic corticosteroids. Fifty-four samples collected from hospitalized patients were analyzed, and viral pathogens were identified in 45 patients (83.3%) using multiplex PCR assay. HRV-A, -B, and -C were detected in 16 (29.6%), one (1.9%), and 16 (29.6%) patients, respectively. The detection rates of HRV-C were lower in the ICS-treated group compared with those in the ICS-untreated group (p = 0.01), whereas maintenance ICS treatment did not affect the detection rate for viral pathogens in total and HRV-A. Changes in FEV % predicted in patients treated with systemic corticosteroids for 6-8 days (n = 10; median, 4.90%) were higher than those in patients treated for 3-5 days (n = 8; median, - 10.25%) (p = 0.0085). Maintenance ICS reduced the detection rates of HRV (mainly HRV-C) in school-age inpatients with asthma exacerbations, and the treatment periods of systemic corticosteroids during exacerbations affected lung function after HRV-induced exacerbations. The protective effects of corticosteroids on virus-induced asthma exacerbations may be dependent upon the types of viral pathogen.